PEMBELAJARAN TARI BERKONTEKS TEMATIK BERDASARKAN KURIKULUM BERBASIS KOMPETENSI DI TK PEMBINA SINGOROJO KABUPATEN KENDAL (Harmonia: Journal of Arts Research and Education, 2009)
The problems in this research are teachers’ preparation before dancing lesson concerned with(aims, materials, methods) dancing, patterns of using natural potentials in surrounding, andresult of dancing learning with thematic context building on curriculum competition based.This research uses qualitative approach with preparation processes in dance learning, whichconsisted of aim determination, materials and methods, patterns of using natural potentials insurrounding, and result of dancing studies with thematic context building on curriculumcompetition based in TK Negeri Pembina Singorojo Regency of Kendal. Data collectiontechniques are observation, interview, and documentation. Analyzing data done by usinginteractive analysis. The result shows that art education in TK Negeri Pembina SingorojoRegency was in the good track. Stages to get those results were done by choosing the bestmethod such as speech, drill, imam, ngedhe and garingan. They are also determinedmaterials, appropriate with the theme that would be taught, and determined learning aim as anindicator of succeed students’ learning building on curriculum competition based. Usingnatural potentials in surrounding could add students’ knowledge of worldwide, so that it couldmotivate students and growed their confidence as a provision to get dance learning thematiccontext.Kata kunci: pendidikan seni tari, berkonteks tematik, kompetensi.